Sales And Production Cost Applications At Pt. Semarang Delta - Devi Ayu Indriyani; Nuris Dwi Setiawan; Titi Christiana (Journal of Engineering, Electrical and Informatics, 2023)
In processing sales and production data at PT. Delta, is an important activity, where distributed data processing still uses Microsoft Excel and Microsoft Word. Therefore, to make it easier for employees to enter data and sell goods, the author tries to process the data using a computerized system that is more effective and efficient.Data collection and analysis were carried out in an effort to solve this problem. The research method used in making this system, from data collection, problem analysis, system design to system creation, is the observation method, and directly handling sales at PT. Delta. This application system was created using the PHP programming language and the database was processed using Adobe Dreamweaver, Appserv, and MySQL.By using this system, the distribution of sales and production data processing at PT. Delta will be easier and more detailed, making it very easy for employees.